The visit [videorecording (DVD)] - Shyamalan, M. Night; Dejonge, Olivia; Oxenbould, Ed, 2001-; Dunagan, Deanna; McRobbie, Peter, 1943-; Hahn, Kathryn, 1974- (Universal Studios Home Entertainment, 2015)
When Becca and Tyler are sent to their grandparents' secluded Pennsylvania farm for a weeklong stay, they quickly discover something is not right with the elderly couple. Faced with strange rules and increasingly frightening behavior, the children soon realize it will take all their wits to make it home alive.